Modern Methods of Teaching Foreign Languages as an Example of EnglishModern Methods of Teaching Foreign Languages as an Example of English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article describes in detail some methods of effective teaching of English and some of the modern educational technologies used in language and its learning.